2012
DOI: 10.1002/aqc.2241
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of artificial structures on the freshwater pearl mussel Margaritifera margaritifera in the River Dee, Scotland

Abstract: 1. Freshwater pearl mussels (Margaritifera margaritifera) in the River Dee (north-east Scotland) are in decline, and now occur at low densities with poor recruitment levels. The population's deterioration has been attributed to reduced water quality, degraded river-bed habitat and pearl fishing but the specific importance of each of these impacts has not previously been investigated.2. This study focused on the impacts of artificial structures on the River Dee's freshwater pearl mussel population. Natural hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…For example, Johnson and Brown () found that mussel beds were more common in sections of their study stream where the substrate was more stable through time. Likewise, Cooksley et al () demonstrated that Margaritifera margaritifera (freshwater pearl mussel) were absent in unstable areas of high sediment deposition in the River Dee, Scotland. Greater understanding of the potential effects of channel adjustment on mussel assemblages will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Johnson and Brown () found that mussel beds were more common in sections of their study stream where the substrate was more stable through time. Likewise, Cooksley et al () demonstrated that Margaritifera margaritifera (freshwater pearl mussel) were absent in unstable areas of high sediment deposition in the River Dee, Scotland. Greater understanding of the potential effects of channel adjustment on mussel assemblages will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Impoundments, pearl fishing, acidification, eutrophication, siltation, degraded water quality, exotic species, and altered fluvial regimes may all have played roles in the FPM decline (Williams et al , ; Young et al , ; Strayer et al , ), although the exact cause is often unclear. General habitat changes have also been suggested as a reason for declining populations (Ross, ; Cooksley et al , ). Björk () demonstrated a significant decline in an FPM population after forest cover in the catchment changed from deciduous to coniferous.…”
Section: Introductionmentioning
confidence: 99%
“…The sources of pressures that lead to these declines generally come from the catchment into the river (Moorkens, ), with soil disturbance and the addition of artificial fertilizer increasing the sources, and drainage increasing the pathways of fine sediment and nutrients into the rivers. Physical changes to the river can also affect mussel habitat, such as bank protection structures, bridges, and direct damage from dredging (Cooksley et al ., ), all of which change the hydromorphological function of the habitat. Changes in flows at an ecologically relevant level are a key component of freshwater habitat and species decline (Bunn and Arthington, ; Dyson et al ., ).…”
Section: Introductionmentioning
confidence: 99%